EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI HIDUP DAMAI DI KELAS VI SD N 054892 LAU GELUGUR - Dedi Sumantri (CV. Arsy Persada Quality, 2024)
This study aims to improve students' critical thinking skills in the subject of Peaceful Living in grade VI of SDN 054892 Lau Gelugur, Salapian District, Langkat Regency, through the application of the Problem-Based Learning (PBL) model. The PBL model was chosen because it can encourage students to think critically and creatively in solving problems related to the material of Peaceful Living. The research was conducted in two cycles, each of which consisted of planning, implementation, observation, and reflection. The results of data analysis showed a significant increase in student learning outcomes, with an average score before the implementation of PBL of 70, increasing to 85 after the implementation. In addition, students' enthusiasm for learning also increased, as seen from their active participation during the learning process. The conclusion of this study indicates that the Problem-Based Learning model is effective in improving students' learning outcomes in the subject of Peaceful Living. It is hoped that the results of this study can provide a positive contribution to educators in designing more interactive and relevant learning.